Prevalence of Burnout Syndrome among medical students and associated sociodemographic factors (Research, Society and Development, 2022)
Objectives: This study aimed to find out the prevalence of Burnout Syndrome among medical students at a private university that uses the active problem-based learning methodology. Methods: Cross-sectional study conducted with 255 medical students at a private university of Sergipe. The Maslach Burnout Inventory- Student Survey and a sociodemographic questionnaire were used. Results: Based on the three-dimensional criterion, 12.2% participants were detected suggestive of having Burnout Syndrome; and according to the two-dimensional criterion, 25.9% were suggestive of having Burnout Syndrome. Conclusion: Among the criteria to investigate the prevalence of Burnout Syndrome, using the three dimensions of Burnout Syndrome together provides greater reliability in the investigation. Our study found a low suggestion rate of Burnout Syndrome when compared to previous literature on the subject, but the percentage found is still worrisome, considering the deleterious condition caused by the disease.